IMPLEMENTASI SISTEM KEUANGAN DESA (SISKEUDES) DALAM MENINGKATKAN AKUNTABILITAS DESA PARIGI KECAMATAN CIKANDE - Lestari, Nida Silvia; Anjani, Anjani; Dentapraja, Dentapraja (Ensiklopedia of Journal, 2025)
Village financial management is one of the key indicators of accountability in village governance. The Village Financial System (Siskeudes), developed by the Financial and Development Supervisory Agency (BPKP) in collaboration with the Ministry of Home Affairs, is designed to facilitate the planning, budgeting, administration, and reporting of village finances in a transparent, accountable, and timely manner. This study aims to analyze the implementation of Siskeudes in enhancing the accountability of Parigi Village, Cikande District, Serang Regency, using Edward III’s policy implementation framework, which consists of four dimensions: communication, resources, disposition, and bureaucratic structure. The research employs a descriptive qualitative approach with data collection techniques including interviews, observations, and document studies. The findings indicate that the implementation of Siskeudes in Parigi Village has performed reasonably well in the areas of communication and disposition but still faces challenges related to the limited number of competent human resources and the availability of supporting infrastructure. The study recommends strengthening the capacity of village apparatus through continuous training and improving competency-based recruitment regulations for village officials.Keywords: Village Financial System, Siskeudes, Accountability, Financial Governance.